56 Determining the energy value of dried corn gluten feed in forage-based beef rations. (7th December 2018) - Hardin, K; Langford, T; Barry, G; Sims, W; White, R; Greiner, S; Fiske, D; Wilson, T
Abstract: Forty-two Angus × Simmental steers (382 ± 8 kg; 13.8 ± 0.4 mo) were individually fed to quantify the energy value of corn gluten feed (CGF ) relative to corn in forage-based beef rations when fed at 3 levels of supplement DMI. Treatments were arranged in a 2 × 3 factorial design with 2 supplement types and 3 levels of supplement DMI. Either cracked corn or pelleted CGF was supplemented at 0.14% (L ), 0.56% (M ), or 0.96% (H ) of BW daily to steers fed ad libitum mixed-grass hay for 63 d. Steers were housed in a dry lot facility equipped with Calan gates. Steer BW and flesh scores (FS ) were recorded on 2 consecutive d at the beginning and end of the experiment and every 14 d. Supplement DMI was adjusted after each interim BW was recorded. There were no interactions ( P ≥ 0.103) between supplement type and level. Initial BW, final BW, and FS were not different ( P ≥ 0.226) by supplement type or level. Steer ADG was greater ( P = 0.034, 0.13 kg/d) with CGF supplementation and increased ( P < 0.001) as level of supplementation increased. Steers supplemented CGF tended to have greater ( P = 0.090) hay DM disappearance than steers supplemented corn. Supplement type did not affect supplemental G:F ( P = 0.305). Supplemental G:F decreased ( P < 0.001) as level of supplementation increased. Observed BW and DMI were entered into the 2016 Beef Cattle Nutrient Requirements Model (BCNRM). The TDN values of corn and CGF were adjusted until observed ADG was correctly predicted by the 2016 BCNRM. The resulting TDN values of corn-L, corn-M, corn-H, CGF-L, CGF-M, and CGF-H were 233%, 102%, 79%, 235%, 120%, and 91%, respectively. The energy values of CGF relative to corn were 101%, 117%, and 115% for L, M, and H, respectively.